Cocaine Paired Environment Increases SATB2 Levels in the Rat Paraventricular Thalamus - Salti, Ahmad; Apostolova, Galina; Kummer, Kai K.; Lemos, Cristina; Dechant, Georg; El Rawas, Rana (Frontiers in Behavioral Neuroscience, 2018)
SATB2 is a DNA binding protein that specifically binds the nuclear matrix attachment region and functions as a regulator of the transcription of large chromatin domains. Unlike its well addressed role during brain development, the role of SATB2 in adult brain is under-investigated. It has been shown that deletion of SATB2 from the forebrain of adult mice significantly impaired long-term memory for contextual fear and object recognition memory. The aim of the present study was to investigate the effects of appetitive stimuli such as cocaine and social interaction (SI) on SATB2 expression in the adult rat brain. For that, we performed conditioned place preference (CPP) to cocaine (15 mg/kg) and to SI, then assessed SATB2 expression in the brain 1 h (24 h after the last conditioning) and 24 h (48 h after the last conditioning) after the CPP test. We found that SATB2 expression in the paraventricular thalamus of rats was increased 1 h after the cocaine CPP test. This increase was selective for the cocaine-paired environment since the SI-paired environment did not increase SATB2 expression in the paraventricular thalamus. Also, the cocaine paired environment-induced increase of SATB2 levels in the paraventricular thalamus was due to cocaine conditioning as the unpaired cocaine group did not show an increase of SATB2 in the paraventricular thalamus. These results suggest that SATB2 in the paraventricular thalamus appears to be involved in the association between cocaine effects and environmental context. Further studies are needed to address the functional role of SATB2 in cocaine conditioning.